Changes in Serum Levels of Type-III Interferons in Ankylosing Spondylitis Treated With Tumor Necrosis Factor-Alpha Inhibitors - Da-min JIAO,; Qiong-jie CHANG,; Ping LI, (Archives of Rheumatology, 2019)
Objectives: This study aims to determine the changes in serum levels of type-III interferons (type-III IFNs) in ankylosing spondylitis (AS) patients treated with tumor necrosis factor-α inhibitors and analyze the correlations between serum type-III IFN levels and disease activity. Patients and methods: The study included 57 AS patients (51 males, 6 females; mean age 29.7±7.0 years; range, 18 to 50 years), who had been diagnosed with AS and had active disease before the start of the study (median disease duration: four years, range 1.3 to 8.0 years). Control group included 50 healthy, age- and sex-matched individuals (45 males, 5 females; mean age 25.5±6.7 years; range, 18 to 55 years). The enzyme-linked immunosorbent assay was used to assess the serum interleukin (IL)-29, IL-28A, and IL-28B levels of AS patients at baseline and first, third, sixth months after treatment with tumor necrosis factor-α inhibitors. Clinical and laboratory features of the disease were also evaluated for AS patients at baseline and first, third, sixth months after treatment. Results: Serum IL-28A levels were significantly higher in AS patients (354.8±164.0 pg/mL) than in controls (257.2±99.6, p=0.003) at baseline. Serum IL-28B levels were significantly lower in AS patients (median, 491.4 pg/mL, range 296.6 to 944.6 pg/mL) than in controls (1121.1±409.3 pg/mL, p=0.000) at baseline. Serum IL-29 levels at third month after treatment (median 430.9, range 277.4 to 1023.9 pg/mL) were significantly increased compared with baseline (median 399.1, range 261.2 to 826.7 pg/mL), p=0.002) and controls (335.2±100.5 pg/mL, p=0.041). There was no association between serum type-III IFN levels and disease activity indexes at baseline. Serum levels of IL-28A were negatively correlated with erythrocyte sedimentation rate levels at first and sixth months after treatment (r=-0.266, p=0.046; r=-0.286, p=0.034, respectively). Serum levels of IL-28A were negatively correlated with Bath Ankylosing Spondylitis Disease Activity Index at third month after treatment (r=-0.269, p=0.043). Serum levels of IL-29 were negatively correlated with Bath Ankylosing Spondylitis Disease Activity Index at third month after treatment (r=-0.299, p=0.024). There was a significant increasing trend for serum IL-28B after tumor necrosis factor-α inhibitors treatment in AS patients, opposite to the decreasing trend for disease activity. Conclusion: These findings indicate that type-III IFNs may be involved in the pathogenesis of AS. Thus, type-III IFNs may provide new targets for the treatment of AS.